Nation, diaspora, trans-nation : reflections from India - Jain, Ravindra K. (New Delhi : Routledge, 2010)
Research articles on Indian diaspora.
Includes bibliographical references(p. [138]-153) and index.
Keywords: East Indian diaspora; East Indians -- Migration; Transnationalism